2022
DOI: 10.1093/braincomms/fcab306
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative susceptibility mapping reveals alterations of dentate nuclei in common types of degenerative cerebellar ataxias

Abstract: The cerebellar nuclei are a brain region with high iron content. Surprisingly little is known about iron content in the cerebellar nuclei and its possible contribution to pathology in cerebellar ataxias, with the only exception of Friedreich’s ataxia. In the present exploratory cross-sectional study, quantitative susceptibility mapping was used to investigate volume, iron concentration and total iron content of the dentate nuclei in common types of hereditary and non-hereditary degenerative atax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 77 publications
6
33
0
Order By: Relevance
“…First, dentate susceptibility mass in SCA6 was markedly reduced relative to those found in the SCA3 and control groups. This finding replicates those from a previous study ( Deistung et al, 2022 ), with significant iron loss in the dentate observed in SCA6, but not in SCA3. Second, susceptibility mass levels in BG regions did not differ across groups, but associations with supplemental measures did.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…First, dentate susceptibility mass in SCA6 was markedly reduced relative to those found in the SCA3 and control groups. This finding replicates those from a previous study ( Deistung et al, 2022 ), with significant iron loss in the dentate observed in SCA6, but not in SCA3. Second, susceptibility mass levels in BG regions did not differ across groups, but associations with supplemental measures did.…”
Section: Discussionsupporting
confidence: 92%
“…Structural volume measures in this study also revealed group differences. The cerebellar dentate was smaller in the SCA6 group than in the SCA3 or healthy control groups, consistent with a recent study that examined the dentate specifically ( Deistung et al, 2022 ). The PT was smaller in both SCA groups relative to the healthy control group.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations